2023
DOI: 10.3897/folmed.65.e69913
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization methods in patients with carotid stenosis and concomitant coronary heart disease

Abstract: A major feature of the atherosclerotic process is its systemic and progressive character. The plaque pathogenetic mechanisms, morphology, evolution, and predilection site (bifurcation zones) determine the frequent coincidence of carotid and coronary atherosclerosis in the same patient. The present overview chronologically traces the history, effectiveness, and benefit of surgical and continuously improving interventional carotid revascularization. It thereby analyzes the indications, results, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…The 6.1-year survival rate was 95.6 ± 3.2% in group A and 89.7 ± 3.7% in group B. This study proved that selective coronary angiography followed by myocardial revascularization prior to CEA in patients with asymptomatic coronary artery lesions is safe and can improve long-term survival and freedom from MI [19].…”
Section: The Incidence Of Coronary Artery Lesions In Patients With At...mentioning
confidence: 52%
See 2 more Smart Citations
“…The 6.1-year survival rate was 95.6 ± 3.2% in group A and 89.7 ± 3.7% in group B. This study proved that selective coronary angiography followed by myocardial revascularization prior to CEA in patients with asymptomatic coronary artery lesions is safe and can improve long-term survival and freedom from MI [19].…”
Section: The Incidence Of Coronary Artery Lesions In Patients With At...mentioning
confidence: 52%
“…The importance of preoperative diagnosis and revascularization of coronary artery lesions in patients with severe carotid artery lesions was reported by Illuminati et al [19]. The RCT included 426 patients without prior angina and myocardial ischemic changes according to ECG and Echo-CG.…”
Section: The Incidence Of Coronary Artery Lesions In Patients With At...mentioning
confidence: 99%
See 1 more Smart Citation
“…Existen varios estudios emblemáticos que han demostrado el beneficio de la CEA en pacientes sintomáticos (26,27). Se ha descubierto que los pacientes que se someten a cirugía y tratamiento farmacológico tienen entre un 9 y un 15% de riesgo de sufrir un accidente cerebrovascular recurrente, que se reduce significativamente en comparación con el riesgo >25% del tratamiento farmacológico solo (28).…”
Section: Manejo De La Estenosis Sintomática De La Arteria Carótidaunclassified
“…One of the main characteristics of atherosclerosis is its systematic and progressive nature. The pathogenesis, morphology, evolution, and segmental (bifurcation) stability of plaque determine the occurrence and development of complications of carotid and coronary atherosclerosis in patients (3). Research showed that an association was observed between the neovascularization and stability of carotid artery plaques and the progression of coronary artery disease (4).…”
Section: Introductionmentioning
confidence: 99%